GINGIVECTOMY IN GINGIVAL ENLARGEMENT CASES USING CONVENTIONAL TECHNIQUE : Gingivektomi Pada Kasus Gingival Enlargement Menggunakan Teknik Konvensional - Made deby artika (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: Gingival enlargements is an abnormal condition that localizedor generalized on the gingival cause by some factor. Gingival enlargements isalways associated with chronic gingival irritation due to traumatic occlusion,calculus and the presence of rough edges on tooth restoration, drug inducedor cause by systemic disease. Gingivectomy is an excision in the gingivalarea. By removing the pocket wall, gingivectomy provides visibility andaccessibility to the removal of calculus as a whole. Case: A 12th years oldmen came to the Klungkung District Hospital complaining of a lump in theupper front gum since 6 months ago, clinically there was gingival swelling at11,12,13,21,22,23. Case Treatment: The treatment procedure performedwas gingivectomy with an conventional technic. Conventional Technic areused routinely for surgical procedures because predictable result. Examplefor Growth excision, excision or incision biopsy, white lesion ablation, andgingivectomy are common in intraoral procedures. Discussions: The resultsof treatment after one week and two weeks showed good condition withslight complaints of pain. Conclusion: The gingivectomy technique in thiscase was performed using a continuous technique because the gingival enlargement was found in the marginal and interdental areas. The results oftreatment for more than a week show good condition.